The exon-skipping oligonucleotide, KitStop, depletes tissue-resident mast cells in vivo to ameliorate anaphylaxis - Hedgespeth, Barry A.; Snider, Douglas B.; Bitting, Katie J.; Cruse, Glenn (Frontiers in Immunology, 2023)
Anaphylaxis represents the most extreme and life-threatening form of allergic disease and is considered a medical emergency requiring immediate intervention. Mast cell-mediated anaphylaxis most commonly occurs following cross-linking of the high-affinity IgE receptor (FcεRI) on the cell surface with allergen-IgE complexes; however, non-IgE-mediated and idiopathic mast cell activation also contribute to the incidence of anaphylaxis. Common triggers include medications, food, and hymenopteran venom. In addition, some people with mastocytosis experience recurrent episodes of anaphylaxis during normal daily activities without exposure to known triggers. While acute therapy consists primarily of epinephrine and supportive care, chronic therapy relies mostly on desensitization and immunotherapy against the offending allergen, which is a time-consuming and sometimes unsuccessful process. These treatments also necessitate identification of the triggering allergen which is not always possible. Here, we report the use of an exon-skipping oligonucleotide, which we have previously termed KitStop, to safely reduce the severity and duration of the anaphylactic response via mast cell depopulation in tissues. KitStop administration results in the integration of a premature stop codon within the mRNA transcript of the KIT receptor—a receptor tyrosine kinase found primarily on mast cells and whose gain-of-function mutation can lead to systemic mastocytosis. Following either local or systemic KitStop treatment, mice had significantly reduced mast cell numbers in the skin and peritoneum. In addition, KitStop-treated mice experienced a significantly diminished anaphylactic response using a model of passive systemic anaphylaxis when compared with control mice. These data demonstrate that KitStop has the potential to serve as a powerful additional treatment modality for patients that suffer from anaphylaxis.